Development of Operational Standards for Risk-Based Cultural Heritage Office Building Maintenance Procedures That The Building Safe and Comfortable to use (Study Case Heritage Office Building PT.X) - Yunita Dian Suwandari; Leni Sagita Riantini (AIBPM Publisher, 2019)
Maintain a sustainable heritage building is currently a crucial challenge.The heritage building is unique from its structure and values such as a historical, education, aesthetics, economy, architecture,community and it requires special handling. One of the problems of heritage buildings in the absence of operational standards (SOP) for maintenance in Indonesia. The purpose of this study to develop a standard operational model maintenance heritage building of risk-based.The research data compose literature review, questionnaires, and qualitative risk data analysis.The risk analysis identified 20 risks of 40 risks variables have the highest risk rank. The result of the study established a risk-based SOP heritage building maintenance.The conclusion it can help to build management in improving the quality of heritage building maintenance practise.